Information resources management : global challenges - Law, Wai K., 1955- (Hershey : Idea Group Publishing, 2007)
'This book addresses challenges in managing information resources in dynamic social environments across cultures, including research on key factors for social acceptance of information technology, and user adoption of information management methods. It explores new paradigms under which information resources will generate original meanings for a contemporary generation of users, with emphasis on user-centered and culture-centric information systems'--Provided by publisher
Includes bibliographical references and index
Keywords: Knowledge management; Information resources management; Information networks -- Management